ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN KINERJA PERAWAT UGD DI RUMAH SAKIT UMUM DAERAH LABUANG BAJI MAKASSAR - Nursyamsiyah Nursyamsiyah; Nur Qamariyah (Lembaga Pengembangan Kinerja Dosen, 2022)
The purpose of the research is to analyze factor analysis that associated to Fadliyah P2MK 16.02.04.026. Factor analysis associated to ICU nurses’s performance at LabuangBaji Hospital in Makassar. This research is under observation without taking interventionwith descriptive observational studiesand carry out observations with cross sectional. The sample of the study was the emergency room nurse in LabuangBajiHospital in Makassaramounted to 35 persons. Data collection was done by questionnaire and interview. As for data analysis technique is chi square test and hypothesis test used is simple regency analysis. Sampling technique was in total sampling. The result showed that education, motivation and years of service had a positive and significant influence with the performance of nurses and the effect was in the good category indicated by logistic regression equation. So, it is suggested that the need for education, motivation and years of service in an effort to improve the performance of nurses, it is hoped to improve the ability through formal and informal education and training as well as conducting comparative satudies (benchmarking).